2019
DOI: 10.1016/j.bbrep.2019.100640
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with DPP-4 inhibitor linagliptin and SGLT2 inhibitor empagliflozin attenuates neointima formation after vascular injury in diabetic mice

Abstract: Incretin therapy has emerged as one of the most popular medications for type 2 diabetes. We have previously reported that the dipeptidyl peptidase-4 (DPP-4) inhibitor linagliptin attenuates neointima formation after vascular injury in non-diabetic mice. In the present study, we examined whether combined treatment with linagliptin and the sodium glucose cotransporter 2 (SGLT2) inhibitor empagliflozin attenuates neointima formation in diabetic mice after vascular injury. Diabetic db/db mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 27 publications
1
37
0
1
Order By: Relevance
“…Empagliflozin was diluted in the drinking water (0,073 mg/ml) and given at a dose of 35 mg/kg body weight per day; at a similar dose range reported by others 11,12 . Empaglifozin was given in the drinking water to replicate the route of intake in humans and to avoid the stress associated with parenteral administration.…”
Section: Methodsmentioning
confidence: 93%
“…Empagliflozin was diluted in the drinking water (0,073 mg/ml) and given at a dose of 35 mg/kg body weight per day; at a similar dose range reported by others 11,12 . Empaglifozin was given in the drinking water to replicate the route of intake in humans and to avoid the stress associated with parenteral administration.…”
Section: Methodsmentioning
confidence: 93%
“…Cell proliferation assays were performed as described previously [6,7] with minor modifications. Briefly, RASMCs were seeded in 12-well tissue culture plates and maintained in complete media with or without 1-1000 nM pemafibrate or 100-500 μM bezafibrate (#022-16091, Fujifilm Wako Chemicals, Osaka, Japan).…”
Section: Proliferation Assaymentioning
confidence: 99%
“…Fourth, as far as we know, there are two reports to show that SGLT2 inhibitors suppressed the neointimal hyperplasia after arterial injury in rodent models [44, 45]. One study showed that ipragliflozin, an oral inhibitor of SGLT2 attenuated cuff-induced femoral artery remodeling in western diet-fed mice partly via increase in adipocyte size of abdominal PVAT with reduced secretion of pro-inflammatory factors [44].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of SGLT2 inhibitors on adipocytes may differ among the location of PVAT; howerver, we did not know the exact reason for the discrepant effects of SGLT2 inhibitors on adipocyte size and pro-inflammatory factors among abdominal, thoracic, and femoral PVAT. Furthermore, since the other study suggested the direct growth inhibitory effect of empagliflozin on smooth muscle cells [45], it would be interesting to clarify the effects of luceogliflozin on PDGF-B-induced smooth muscle cell proliferation and migration in vitro.…”
Section: Discussionmentioning
confidence: 99%